Faktor-Faktor Yang Memengaruhi Profitabilitas PT Bank Negara Indonesia Tbk. 2017-2022 - Wulandari, Sri; Ritha, Henny (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2023)
This study aims to analyze the Factors Affecting the Profitability of PT Bank Negara Indonesia 2017-2022. The type of research data is quantitative, and the secondary data source consists of the financial statements of PT Bank Negara Indonesia Tbk. 2017-2022. Technique analysis used panel data regression analysis. The results showed that the Capital Adequacy Ratio (CAR), and Operational Costs and Operating Income (BOPO) had no effect on Return On Assets (ROA), while Net Performing Loans (NPL) had a negative and significant effect on Return On Assets (ROA), and Loan to Deposit Ratio (LDR) has a positive and insignificant effect on Return On Assets (ROA).